Research on optimal collaborative method for microgrid environmental and economic dispatch in grid-connected mode. (26th March 2020) - Chen, Juan; Lu, Bin; Hao, Lingling
In recent years, real-time optimisation of microgrid dispatch with minimal total costs of energy generation and emission has been an urgent problem. In this paper, a collaborative method was considered for microgrid connected mode. At first, we constructed the microgrid schematic diagram of energy flow. Then, a mathematical model was presented for dispatch optimisation environmentally and economically. After defining the objective function according to the energy consumption, maintenance and systemic carbon emissions, two types of constraints were given including the single input-output balance and the overall energy flow balance. Thirdly, we analysed the cooperative co-evolutionary genetic algorithm and applied it to a large number of cases. The better optimisation performance and convergence rate were obtained by comparing the method with the traditional genetic algorithms. The experimental results show it may play a significant role in the optimal scheduling of distributed energy generations in grid-connected mode.